Analisis Strategi Marketing Mix Terhadap Peningkatan Jumlah Pengunjung Pada Cafe Radio Kopi Kebumen - Fakhrurrozi Ibnurrizal; Tri Yulistyawati Evelina; Rizky Kurniawan Murtiyanto (Jurnal Ekonomi dan Bisnis Digital, 2025)
Marketing is an effort to maintain and keep a business growing and can help expand a business. The increasingly rapid development of technology today has created many ways to carry out marketing with the aim of increasing the number of visitors. One of them is by implementing the 7P marketing mix to help increase the number of visitors to Cafe Radio Kopi Gombong, with a focus on providing the best service for consumers. This research aimed to find out how the 7P marketing mix applies to increasing the number of visitors at Cafe Radio Kopi, as well as finding out what factors are obstacles and supporters in this implementation. This research was qualitative research with a description of the 7P variables in the marketing mix, namely product, price, place, promotion, people, process, physical evidence. This research used the data collection techniques of interviews, observation and documentation with purposive sampling techniques. The unit of analysis in this research consisted of 6 informants, consisting of the owner, manager and visitors of Café Radio Kopi. The results of this research used discourse analysis techniques, showed that the marketing mix strategy implemented at Café Radio Kopi to increase the number of visitors in the marketing process was carried out well and healthily by implementing product, price, place, promotion, people, process and physical evidence. The marketing strategy through the marketing mix carried out by Café Radio Kopi used the 7P marketing mix. The results of this research showed that the implementation of the 7P marketing mix applied at Café Radio Kopi Gombong in increasing the number of visitors is very good and has good procedures for dealing with customers, in order that customers who visit are satisfied with the services provided.